Asymmetric barrier material, preparation thereof and application of asymmetric barrier material in aqueous asymmetric zinc metal battery
By using asymmetric barrier materials in zinc metal batteries, combined with cellulose-based film and PVDF-based polymer organic coating, the problem of dendrites growth and deposition inhomogeneity caused by zinc negative electrode side reaction is solved, and the long-range cycle stability of the battery is significantly improved.
Patent Information
- Application Number
- CN202411663626.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-20
AI Technical Summary
The water molecules on the negative electrode side of the zinc metal battery react with the zinc metal, such as corrosion, hydrogen evolution reaction, resulting in uneven dendrites growth and Zn deposition, affecting the long-range cycle stability of the battery.
Asymmetric barrier materials, including cellulose-based films and organic coatings composited on their surfaces, are further optimized by polarization treatment.
It effectively solved the problems of zinc negative electrode hydrogen evolution reaction, dendrite growth and dead zinc evolution, and significantly improved the long-range cycle stability under large currents of zinc metal batteries.
Smart Images

Figure CN119601895A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of zinc metal batteries, and in particular relates to an asymmetric zinc metal battery designed using an asymmetric barrier material. Background Art
[0002] Zinc metal anode has the advantages of low redox potential (-0.76 V relative to standard hydrogen electrode (SHE), high theoretical capacity (820 mAh / g, 5855 mAh / cm3) and safety. Rechargeable aqueous zinc batteries using zinc metal anodes are regarded as the most promising next-generation energy storage battery technology due to their inherent safety, low cost and sustainability. However, as a typical aqueous electrolyte system battery, a long-term challenge faced by zinc batteries in practical applications is the complex reaction of water on the negative electrode side. On the negative electrode side, water molecules react with zinc metal to cause corrosion, hydrogen evolution reaction, etc., resulting in uneven distribution of dendrite growth and Zn deposition. Therefore, it is very necessary to develop reasonable strategies to solve this problem of aqueous zinc batteries.
[0003] Electrolyte strategy is an important strategy to solve the above problems of aqueous zinc metal batteries. For example, the invention patent CN118800980A designs an aqueous electrolyte with silicate additives. The additives reduce the interface side reactions by inhibiting the activity of water. An organic electrolyte for zinc batteries with chlorophyll derivatives as additives was designed, which greatly promoted the transmission rate of zinc ions in the organic electrolyte, increased the ionic conductivity, and improved the reversibility of zinc ions.
[0004] In addition, a Chinese patent document with publication number CN117712622A discloses an asymmetric diaphragm and its preparation method and application. The asymmetric diaphragm is made of waste animal and plant fibers as raw materials and combined with Lewis acid and Lewis base, and is prepared by layer-by-layer electrospinning or vacuum filtration. The pores of the asymmetric diaphragm are small on both sides and large in the middle; the two sides of the asymmetric diaphragm are mainly Lewis acid or base, and the middle is mainly animal / plant fibers.
[0005] In summary, although there are some improvement schemes for electrolytes and diaphragms in the prior art, it is difficult to properly adapt to the application requirements of aqueous zinc batteries, and it is difficult to fundamentally solve the problems of hydrogen evolution reaction, dendrite growth, and dead zinc evolution at the zinc negative electrode. Summary of the invention
[0006] In order to solve the problems of hydrogen evolution reaction, dendrite growth, dead zinc evolution, etc. at the zinc negative electrode and to improve the service life of zinc metal batteries, the first purpose of the present invention is to provide an asymmetric barrier material, aiming to provide a barrier material that is adapted to the application requirements of asymmetric aqueous zinc batteries, can effectively solve the problems of hydrogen evolution reaction, dendrite growth, dead zinc evolution at the zinc negative electrode, and thus significantly improve its long-term cycle stability.
[0007] The second object of the present invention is to provide the preparation of the asymmetric barrier material and its application in an asymmetric aqueous zinc battery.
[0008] A third object of the present invention is to provide an asymmetric aqueous zinc battery comprising the asymmetric barrier material.
[0009] Aiming at the problems of zinc negative electrode hydrogen evolution reaction, dendrite growth, dead zinc evolution, and unsatisfactory high current long cycle performance faced by zinc metal batteries, the present invention provides the following solutions after in-depth research:
[0010] An asymmetric barrier material comprises a cellulose-based film and an organic coating compounded on the surface thereof, wherein the organic coating comprises a PVDF-based polymer and a conductive zinc salt distributed therein.
[0011] The present invention provides an asymmetric barrier material with a new physicochemical structure, which is based on the combination of a base film and an organic coating and can unexpectedly adapt to the application requirements of aqueous zinc metal batteries, can help solve the problems of zinc negative electrode hydrogen evolution reaction, dendrite growth, dead zinc evolution, etc., and helps to improve the long-range cycle stability of zinc metal batteries under high current.
[0012] In the present invention, the cellulose-based membrane may be any cellulose-based membrane recognized in the industry, for example, a base membrane of ordinary cellulose or glass cellulose, and the thickness thereof may be 10 to 50 μm, and further may be 20 to 30 μm.
[0013] In the present invention, the PVDF-based polymer includes one or more of PVDF, P(VDF-TrFE), P(VDF-HFP), P(VDF-TrFE-CTFE), etc.; further, P(VDF-TrFE), P(VDF-HFP), P(VDF-TrFE-CTFE); further, at least one of P(VDF-TrFE) and P(VDF-TrFE-CTFE) having relaxor ferroelectric function. Studies have shown that the multiphase PVDF-based polymer is preferably used in conjunction with the process of the present invention to further enhance the adaptability of zinc metal batteries, help further solve the problems faced by zinc metal batteries, and help further improve the long-range cycle performance of zinc metal batteries under high current.
[0014] In the present invention, the conductive zinc salt includes one or more of zinc trifluoromethanesulfonate, bis(trifluoromethanesulfonyl) zinc, and zinc acetate.
[0015] Preferably, the weight ratio of the PVDF-based polymer to the conductive zinc salt is 1:0.05-0.8, and can further be 1:0.1-0.5.
[0016] Preferably, the thickness of the organic coating is 1 to 20 μm, and further can be 1 to 5 μm.
[0017] In a preferred embodiment of the present invention, the asymmetric barrier material is a material that has been subjected to polarization treatment.
[0018] Further preferably, the polarization electric field is 60-100 KV / mm, preferably 85-100 KV / mm, and further 94-96 KV / mm. Studies have shown that under the preferred polarization process, it can further help solve the problems faced by zinc metal batteries and help further improve the long-range cycle performance of zinc metal batteries under high current.
[0019] More preferably, the polarization time is 5 to 30 min, and further can be 10 to 15 min.
[0020] The present invention also provides a method for preparing the asymmetric barrier material, the preparation steps of which are: slurrying a PVDF-based polymer and a conductive zinc salt and coating the slurry on a cellulose-based film, followed by drying; or, subjecting the prepared asymmetric barrier material to polarization treatment.
[0021] The present invention also provides an application of the asymmetric barrier material, which is arranged between a positive electrode and a negative electrode to prepare the aqueous zinc metal battery.
[0022] The present invention also provides an aqueous asymmetric zinc metal battery, comprising a positive electrode, a barrier layer, and a negative electrode composite battery cell, wherein the barrier layer is the asymmetric barrier material of the present invention, wherein the cellulose-based film of the asymmetric barrier material is arranged near the positive electrode side, and the organic coating of the asymmetric barrier material is arranged near the negative electrode side;
[0023] The positive electrode is immersed in an aqueous electrolyte;
[0024] The negative electrode is not immersed in an aqueous electrolyte or immersed in an organic electrolyte.
[0025] The research of the present invention shows that the asymmetric barrier material of the present invention, in combination with the setting mode of the asymmetric structure, can further enhance the synergy, help to further fundamentally solve the problems of zinc negative electrode hydrogen evolution reaction, dendrite growth, dead zinc evolution, etc., and can significantly improve the long-range cycle performance of the prepared battery.
[0026] In the present invention, the aqueous electrolyte is an aqueous solution of zinc ions;
[0027] Preferably, the concentration of zinc ions in the aqueous solution of zinc ions is 0.5-3M.
[0028] In the present invention, the organic electrolyte is a mixed solution of an organic zinc salt and an organic solvent, wherein the organic solvent is one or more of acetonitrile, dimethylacetamide, and dimethylformamide; the organic zinc salt is one or more of zinc trifluoromethanesulfonate, bistrifluoromethanesulfonyl zinc, and zinc acetate;
[0029] The concentration of the organic zinc salt is 0.5~3M.
[0030] In the present invention, the positive electrode can be any known positive electrode sheet known in the field of aqueous zinc batteries. For example, it can include a current collector and a positive electrode material composited on its surface. The positive electrode material can include a positive electrode active material of a zinc metal battery, a conductive agent and a binder.
[0031] The negative electrode of the present invention may be a zinc metal negative electrode.
[0032] Beneficial Effects
[0033] The present invention provides an asymmetric barrier material suitable for aqueous zinc batteries, which, based on the combination of components and structures, helps to solve the problems of zinc negative electrode hydrogen evolution reaction, dendrite growth, dead zinc evolution, etc.; in addition, the present invention pre-polarizes the components of the organic coating, which can further enhance the performance of the material in aqueous zinc batteries.
[0034] The research of the present invention also shows that combining the barrier material and the physical and chemical structure of the battery can further enhance the synergy, help to further fundamentally solve the problems of zinc negative electrode hydrogen evolution reaction, dendrite growth, dead zinc evolution, etc., and can significantly improve the long-range cycle performance of the prepared battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 Full battery cycle performance diagram of Example 1 and Comparative Example 1;
[0036] Figure 2 Surface morphology of the asymmetric barrier material in Example 1; DETAILED DESCRIPTION
[0037] An optional asymmetric barrier material of the present invention comprises the following steps:
[0038] I. mixing a PVDF-based polymer and an organic solvent in a certain proportion to form a solution A;
[0039] II. dissolving an organic zinc salt into solution A to form a polymer electrolyte precursor solution B;
[0040] III. coating the precursor solution B on the surface of the cellulose membrane;
[0041] IV. Drying the diaphragm coated with the electrolyte precursor in a closed vacuum environment, drying at a high temperature, and evaporating the organic solvent to obtain an asymmetric barrier material.
[0042] The PVDF-based polymer described in step I includes one or more of PVDF, P(VDF-TrFE), P(VDF-HFP), P(VDF-TrFE-CTFE) and the like.
[0043] The organic solvent in step I is one or more of N,N-dimethylformamide DMF, N,N-dimethylacetamide DMA, N-methylpyrrolidone NMP, etc., preferably N,N-dimethylformamide DMF, N,N-dimethylacetamide DMA.
[0044] The mass ratio of PVDF-based polymer to organic solvent is (0.1~2):1.
[0045] In step II, the organic zinc salt is one or more of zinc trifluoromethanesulfonate Zn(CF3SO3)2, bis(trifluoromethanesulfonyl zinc) Zn(TFSI)2, and zinc acetate Zn(CH3COO)2, preferably zinc trifluoromethanesulfonate Zn(CF3SO3)2 and bis(trifluoromethanesulfonyl zinc) Zn(TFSI)2, with a concentration of 0.5~3M.
[0046] The cellulose membrane described in step III is one of a common cellulose membrane or a glass cellulose membrane. In the following cases, as an optional solution, its thickness can be 20±2 μm, preferably a GFD glass cellulose membrane;
[0047] The temperature described in step IV is 45~100°C and the vacuum environment.
[0048] Embodiment 1:
[0049] The mass ratio of polymer polyvinylidene fluoride-trifluoroethylene P(VDF-TrFE) and organic matter N,N-dimethylformamide DMF is controlled to be 0.5:1, and mixed to form solution A; then 1M zinc trifluoromethanesulfonate Zn(CF3SO3)2 is added to form a mixed solution B (the weight ratio of polymer: zinc trifluoromethanesulfonate is 1:0.5), and the mixed solution B is coated on one surface of a base film (GFD glass cellulose) with a coating thickness of 3μm. It is then placed in a vacuum environment and dried at 60°C for 10h to form an organic coating on the surface of the base film. It is then polarized at a voltage of 95KV / mm for 10min to obtain an asymmetric barrier material.
[0050] test:
[0051] V2O5 was used as the positive electrode, and the mass ratio of V2O5: carbon black: PVDF was 7:2:1. The mixture was uniformly prepared into a slurry, which was uniformly coated on a titanium foil, which was cut into a positive electrode sheet with a diameter of 12 mm. A zinc metal sheet was used as the negative electrode, and a CR2025 button battery was assembled in the air. The positive electrode was assembled first, and then an aqueous electrolyte (1M zinc sulfate aqueous solution) was added to wet the positive electrode, and then an asymmetric barrier material was added, wherein the fiber membrane layer (base membrane) of the asymmetric barrier material was close to the positive electrode side, and the P (VDF-TrFE)-based electrolyte (organic coating) faced the zinc negative electrode, and the negative electrode shell was covered, and the whole battery was packaged by a press. This is Example 1. The battery made of an aqueous electrolyte and a common GFD separator is a comparative battery.
[0052] Comparative Example 1
[0053] Compared with Example 1, the only difference is that when assembling the battery, the barrier layer is the base film (GFD glass cellulose before modification of Example 1) separator, the positive electrode and the negative electrode are both immersed in the aqueous electrolyte, and the rest is the same as Example 1.
[0054] The above batteries were subjected to charge and discharge cycle tests under the same test equipment and test conditions, wherein the voltage range of the full battery test was 0.2~1.6V and the test temperature was 25℃. Figure 1 The battery capacity of Example 1 is 260.8 mAh g at a current density of 1 A / g. -1 After 1500 cycles, the capacity is still 117.8 mAh g -1 The retention rate is 45.2%, while the initial capacity of comparative example 1 is 228.3 mAh g -1 After 365 cycles, only 10% of the capacity remains.
[0055] Embodiment 2:
[0056] Compared with Example 1, the only difference is that the polarization condition is changed, and other operations, parameters and tests are the same as those in Example 1, specifically:
[0057] A: Polarized at 70KV / mm for 30 min. Its capacity is 248.3 mAh g at a current density of 1A / g. -1 After 1500 cycles, the capacity retention rate is 33.8%.
[0058] B: Polarized at 90KV / mm for 10 min. Its capacity is 254.6 mAh g at a current density of 1A / g. -1 After 1500 cycles, the capacity retention rate is 41.6%.
[0059] C: no polarization treatment;
[0060] Its capacity is 242.6 mAh g at a current density of 1 A / g. -1 After 1500 cycles, the capacity retention rate is 30.7%.
[0061] It can be seen from Examples 1 and 2 that polarization treatment of the barrier layer can optimize the long cycle performance of the prepared asymmetric battery.
[0062] Embodiment 3:
[0063] Compared with Example 1, the only difference is that the polymer is changed, and the other operations, parameters and tests are the same as Example 1. The experimental groups are:
[0064] Group A: The polymer is P(VDF-TrFE-CTFE). Its capacity is 257.9 mAh g at a current density of 1 A / g. -1 After 1500 cycles, the capacity retention rate is 44.8%.
[0065] Group B: The polymer is PVDF, and its mass ratio remains unchanged. Its capacity is 239.5 mAh g at a current density of 1 A / g -1 After 1500 cycles, the capacity retention rate is 34.1%.
[0066] It can be seen from Examples 1 and 3 that the long cycle performance of the prepared asymmetric battery can be further optimized by using the process described in the present invention in combination with the combination of the multiphase polymers.
[0067] Embodiment 4:
[0068] Compared with Example 1, the only difference is that the following conditions are changed, specifically: the organic solvent is replaced by N,N-dimethylacetamide DMA, the ratio of polymer to organic solvent is 1:1; the base membrane is GFA diaphragm; the weight ratio of polymer to organic zinc salt is 1:0.2; the drying temperature after coating is 90°C and the time is 10h; other operations and parameters are the same as Example 1.
[0069] The results show that the capacity is 254.6 mAh g at a current density of 1 A / g. -1 After 1500 cycles, the capacity retention rate is 42.1%.
[0070] Comparative Example 2
[0071] Compared with Example 1, the only difference is that when assembling the battery, the organic coating side of the asymmetric barrier material is close to the positive electrode, and the other operations and parameters are the same as Example 1.
[0072] The results show that the capacity is 207.3 mAh g at a current density of 1 A / g. -1 , and it fails after 500 cycles.
[0073] Comparative Example 3
[0074] Using asymmetric barrier materials, the negative electrode side is additionally added with the same aqueous electrolyte as the positive electrode side. Its capacity is 227.5 mAh g at a current density of 1A / g -1 , and it fails after 400 cycles.
[0075] Comparative Example 4
[0076] Asymmetric barrier material was used, and the organic zinc salt was not added to the organic coating. Other operations and parameters were the same as those in Example 1. The capacity was 201.5 mAh g at a current density of 1 A / g. -1 , the capacity retention rate is 10% after 1500 cycles.
[0077] Comparative Example 5
[0078] Asymmetric barrier material was used, and the polymer in the polymer coating was PAA. Other operations and parameters were the same as those in Example 1. The capacity was 197.3 mAh g at a current density of 1 A / g. -1 After 1500 cycles, the capacity retention rate is 11%.
[0079] Comparative Example 6
[0080] Asymmetric barrier materials were used, the base film was replaced by a PP diaphragm, and other operations and parameters were the same as in Example 1. The capacity reached 223.5 mAh g at a current density of 1 A / g. -1 , and it fails after 150 cycles.
Claims
1. An asymmetric barrier material, characterized in that: The invention comprises a cellulose-based film and an organic coating compounded on the surface of the cellulose-based film, wherein the organic coating comprises a PVDF-based polymer and a conductive zinc salt distributed therein.
2. The asymmetric barrier material according to claim 1, characterized in that: The cellulose-based film is a base film of ordinary cellulose or glass cellulose, and its thickness is >20 μm; Preferably, the PVDF-based polymer includes one or more of PVDF, P(VDF-TrFE), P(VDF-HFP), P(VDF-TrFE-CTFE), etc.; Preferably, the conductive zinc salt includes one or more of zinc trifluoromethanesulfonate, bis(trifluoromethanesulfonyl) zinc, and zinc acetate; Preferably, the weight ratio of the PVDF-based polymer to the conductive zinc salt is 1:0.05-0.8; Preferably, the thickness of the organic coating is 1-20 μm.
3. The asymmetric barrier material according to any one of claims 1 to 2, characterized in that: The asymmetric barrier material is a material obtained by polarization treatment.
4. The polarized asymmetric barrier material according to claim 3, characterized in that: The polarization electric field is 60~100KV / mm, preferably 85~100KV / mm, and further 94~96KV / mm.
5. The polarized asymmetric barrier material according to claim 4, characterized in that: The polarization time is 5 to 30 minutes, and can be further 10 to 15 minutes.
6. A method for preparing the asymmetric barrier material according to any one of claims 1 to 5, characterized in that: The asymmetric barrier material is the asymmetric barrier material according to any one of claims 1 to 2, and the preparation steps are: slurrying a PVDF-based polymer and a conductive zinc salt, coating the slurry on a cellulose-based film, and drying the slurry; Alternatively, the asymmetric barrier material is the asymmetric barrier material according to any one of claims 3 to 5, and the preparation step is: subjecting the prepared asymmetric barrier material to polarization treatment.
7. Use of the asymmetric barrier material according to any one of claims 1 to 5, characterized in that: It is arranged between the positive electrode and the negative electrode to obtain the aqueous zinc metal battery.
8. An aqueous asymmetric zinc metal battery, comprising a positive electrode, a barrier layer, and a negative electrode composite battery cell, characterized in that: The barrier layer is the asymmetric barrier material according to any one of claims 1 to 5, wherein the cellulose-based film of the asymmetric barrier material is arranged near the positive electrode side, and the organic coating of the asymmetric barrier material is arranged near the negative electrode side; The positive electrode is immersed in an aqueous electrolyte; The negative electrode is not immersed in an aqueous electrolyte or immersed in an organic electrolyte.
9. The aqueous asymmetric zinc metal battery according to claim 8, characterized in that: The aqueous electrolyte is an aqueous solution of zinc ions; Preferably, the concentration of zinc ions in the aqueous solution of zinc ions is 0.5-3M.
10. The aqueous asymmetric zinc metal battery according to claim 8, characterized in that: The organic electrolyte is a mixed solution of an organic zinc salt and an organic solvent, wherein the organic solvent is one or more of acetonitrile, dimethylacetamide, and dimethylformamide; the organic zinc salt is one or more of zinc trifluoromethanesulfonate, bis(trifluoromethanesulfonyl) zinc, and zinc acetate; The concentration of the organic zinc salt is 0.5~3M.
Citation Information
Patent Citations
Asymmetric diaphragm as well as preparation method and application thereof
CN117712622A
Novel aqueous zinc ion battery electrolyte additive and application thereof
CN118800980A
Method for prolonging cycle life of zinc battery and application thereof
CN108520985A
Interface-modified metal zinc negative electrode and preparation method thereof
CN113725392A
Zinc ion battery and method for improving cycle performance of zinc negative electrode of zinc ion battery
CN114142032A